1997
DOI: 10.1046/j.1469-7580.1997.19040577.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of pre‐ and postnatal exposure to the nonsteroidal antiandrogen flutamide on testis descent and morphology in the Albino Swiss rat

Abstract: Exposure of male Albino Swiss rats to the nonsteroidal antiandrogen flutamide during the period from gestational day (d) 10 to birth resulted in feminisation of the external genitalia and the suppression of growth of the male reproductive tract. In adulthood, testes were found to be located in diverse positions. True cryptorchidism occurred in 10 % of cases, whereas 50 % of testes descended to the scrotum and 40 % were located in a suprainguinal ectopic region. Varying degrees of tubule abnormality wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
42
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 39 publications
7
42
0
1
Order By: Relevance
“…Undescended testes were smaller in weight than descended testes, and the histological degeneration in the testis was attributed to abdominal cryptorchidism. In a study of flutamide-induced cryptorchidism, Kassim et al (1997) found differences in degree of abnormalities of spermatogenesis, depending on the intra-abdominal position of the testes, which support our findings of testicular degeneration being a secondary change due to abdominal cryptorchidism. Association of the testicular hypospermatogenesis and lower number of sperm in the lumen of the epididymal ductules was evidenced by histological findings at the final necropsy .…”
Section: Discussionsupporting
confidence: 80%
“…Undescended testes were smaller in weight than descended testes, and the histological degeneration in the testis was attributed to abdominal cryptorchidism. In a study of flutamide-induced cryptorchidism, Kassim et al (1997) found differences in degree of abnormalities of spermatogenesis, depending on the intra-abdominal position of the testes, which support our findings of testicular degeneration being a secondary change due to abdominal cryptorchidism. Association of the testicular hypospermatogenesis and lower number of sperm in the lumen of the epididymal ductules was evidenced by histological findings at the final necropsy .…”
Section: Discussionsupporting
confidence: 80%
“…Flutamide's reduction of testes size in the present study ( Figure 1A) is consistent with its effects in developing rats [5,17]. This reduction in testes size can be explained either by flutamide's direct antiandrogenic effect on the testes or by flutamide's up-regulation of aromatase activity and consequent increased E 2 production [16].…”
Section: Discussionsupporting
confidence: 76%
“…However, data were available for rats exposed to flutamide from GD 12 to PND 27 or administered flutamide by injection on PND 1-14 (listed under inguinoscrotal migration in Table 1); all testes completed transinguinal migration and were found in the scrotum at 16-20 week of age. Hence, transinguinal migration of testes occurs in rat pups, at the normal time or with slight delay, with testosterone- Barthold et al (1996); (2) Kassim et al (1997); (3) McMahon et al (1995); (4) Mylchreest et al (1999); (5) Shono et al (1994b); (6) Spencer et al (1991); (7) Spencer et al (1993).…”
Section: Role Of Testosteronementioning
confidence: 99%